Flexible Substrate with Low Reflection, Low Haze, Self‐cleaning, and High Hardness by Nano‐structured Hard Coating and Surface Treatment. Issue 1 (June 2014) - Lan, Yi‐Hsin; Yang, Teng‐Yi; Liu, Yu‐Hao; Lin, Di‐Hong; Wang, Bo‐Hua; Wei, Mao‐Kuo; Chiu, Tien‐Lung; Lin, Chi‐Feng; Peng, Lung‐Han; Cheng, I‐Chun; Li, I‐Yin; Wei, Chung‐Kuang; et al.
Abstract Low reflectance (0.6%), low haze (1.3%), self‐cleaning, and high hardness flexible substrate was fabricated in a simple process including imprinting, curing and etching for obtaining nanostructures on the hard coating.